Pelatihan Implementasi Media Interaktif Wordwall untuk Menciptakan Lingkungan Belajar yang Inovatif dan Kreatif - Firdiawan Ekaputra; Haryanto Haryanto; Wilda Syahri; Afrida Afrida; Isra Miharti (I-Com: Indonesian Community Journal, 2024)
Teachers of SMA Negeri 2 Muaro Jambi do not understand much about interactive media such as wordwall applications and learning media is still dominated by powerpoint media due to the lack of references in developing alternative media that can motivate students in learning. The purpose of this activity is to train the skills of SMA Negeri 2 Muaro Jambi teachers in implementing wordwall interactive media to create an innovative and creative learning environment. The wordwall interactive media implementation training activities were carried out at SMA Negeri 2 Muaro Jambi on July 17, 2024 which was attended by 32 teachers from all subject areas. The methods used in this training include initial analysis which aims to find out the problems in partner schools, implementation, and evaluation of training activities. Based on the training activities that have been carried out, it shows that teachers are very enthusiastic in developing wordwall media. The results of the questionnaire showed that the improvement of teacher skills obtained the highest score of 4.72.